IMPLEMENTASI WEIGHTED PRODUCT DALAM PENENTUAN PEMENANG GIVEAWAY PADA TOKO BOUTIQUE - Ayudita Puspitasari; Lelah Lelah; Prajoko Prajoko (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
The giveaway activity is a marketing activity carried out by a brand with the aim of attracting market attention, and introducing the brand more broadly to potential customers. By distributing prizes to selected customers. In this activity, several problems emerged, namely the Sukabumi Boutique Store admin felt that it was not objective because the process of determining the winner of the giveaway was only through the picker application on the cellphone, so that the giveaway winners who appeared did not pay attention to certain criteria and requirements. Determination through the picker application is only done by drawing a lot by looking at the name that appears first. Selection like this is considered unfair for customers who already feel they meet all the criteria and requirements but do not win the giveaway. In the implementation of the simulation of determining the winner of the giveaway, a method is needed that can solve these problems. The weighted product method is a ranking method where decisions are made by multiplying to connect attribute ratings. This process begins with inputting alternative data, then continues with the process of inputting several criteria that have been selected, namely, number of transactions, quantity of shopping, total visits, resellers. This selection process will determine the giveaway winner in a more targeted and more objective manner by taking into account certain criteria and requirements. Keywords: Giveaway, Weighted Product, Boutique Sukabumi, Picker App